KARAKTERISTIK PERILAKU MINAT KUNJUNGAN GENERASI Z (Gen-Z) PADA EVENT PAMERAN (STUDI KASUS DKI Jakarta) - Mubarak, Fauzi; Judisseno, Rimsky K.; Sudarno, Sudarno; Saputra, Restu Jati (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
This study aims to analyze the behavioral characteristics of Generation Z's (Gen Z) interest in visiting exhibition events in DKI Jakarta. A quantitative descriptive research method was employed, involving 103 respondents aged 20–23 years. The results indicate that Generation Z considers information from exhibitions important (mean 3.46) and shows high interest in participating in seminars/workshops (mean 3.31). Location (mean 3.69) and entry cost (mean 3.38) significantly influence their visitation decisions. Although visitation frequency is low (76.9% visit only 1–2 times/year), Generation Z demonstrates awareness of sustainability practices (mean 3.38), albeit with limited willingness to pay extra for them (mean 2.77). These findings suggest that exhibition organizers should adapt strategies regarding location, pricing, and educational content to attract Generation Z. Further research is needed to generalize the findings with a more diverse sample.